AB0691 Association between MRI Inflammation and Disease Activity in Early Axial Spondyloarthritis. (10th June 2014) - Gubar, E.; Smirnov, A.; Tukhova, E.; Dubinina, T.; Demina, A.; Godzenko, A.; Rumyantseva, O.; Shubin, S.; Gluhova, S.; Erdes, S.
Abstract : Background: The relationship between MRI inflammation and disease activity in early axial spondyloarthritis has not been proved sufficiently. Objectives: Establishing the association between clinical activity and MRI inflammation of sacroiliac joints (SIJs), lumbar spine (LS) and hip joints (HJs) in early axial spondyloarthritis (axSpA) patients (pts). Methods: 73 pts (33 men and 40 women) with early axSpa were examined: disease duration – 19.9±14.4 months. Pts fulfilled ASAS criteria. Age – 28.3±6.4 years, BASDAI – 4.1±1.9; ASDAS-CRP – 2.7±1.3; ESR – 21.9±17.6; CRP – 29.0±38.5; 66 (90.4%) pts were HLA-B27 positive. High disease activity was assumed in cases where BASDAI ≥4, ASDAS-CRP ≥2.1. MRI of SIJs, LS and hip joints (in case of hip joint involvement) was performed on Signa Ovation 0, 35 T scanner (matrix 288x192). Results: MRI inflammation of SIJs and/or LS and/or HJs has been found in 62 (84.9%) pts: SIJs – in 53 (72.6%) pts, HJs – in 21 (28.7%) pts and LS, – in 8 (11.0%) pts. 42 out of 62 (67.7%) pts that had MRI inflammation in at least one of the three studied sections, had high ASDAS-CRP activity; and out of the group of patients without MRI inflammation (n=11) high ASDAS-CRP has been detected in 4 (36.4%) pts (p=0.047). High ASDAS-CRP activity was observed in 38 out of 53 (71.7%) pts that had active sacroiliitis (SI); out of the group of pts without MRI SI (n=20), high ASDAS-CRP was observed in 8 (40.0%) pts (p=0.012). No association has been found between MRI data and disease activity according to BASDAI. Conclusions: Correlation has been detected between inflammatory lesion in SIJs and/or LS and/or HJs and high disease activity according to ASDAS-CRP. There is an association between existence of active MRI SI and high ASDAS-CRP activity. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4134